2014
DOI: 10.1016/j.jfa.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Sharp generalizations of the multilinear Bohnenblust–Hille inequality

Abstract: Abstract. We prove that the multilinear Bohnenblust-Hille is a particular case of a quite general family of optimal inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 13 publications
(14 reference statements)
3
121
0
3
Order By: Relevance
“…In this section we obtain partial answers for the cases not covered by our main theorem, i.e., the cases (r, p) ∈ [1, 2] × [1,2) and (r, p) ∈ (2, ∞) × [1, m]. for all m-linear forms T : n p × · · · × n p → K and all positive integers n. Moreover the optimal exponent of n is not smaller than (2m − r)/2r.…”
Section: Final Comments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we obtain partial answers for the cases not covered by our main theorem, i.e., the cases (r, p) ∈ [1, 2] × [1,2) and (r, p) ∈ (2, ∞) × [1, m]. for all m-linear forms T : n p × · · · × n p → K and all positive integers n. Moreover the optimal exponent of n is not smaller than (2m − r)/2r.…”
Section: Final Comments and Resultsmentioning
confidence: 99%
“…For references we mention, for instance, [2,6,13,14,21] and the very interesting survey [15]. The optimal values of B K,m are unknown; the best known upper and lower estimates for the constants in (1.1) are (see [6,18]):…”
Section: Introduction the Recent Years Witnessed An Intense Interestmentioning
confidence: 99%
“…Hence the assumptions of Theorem 2.1 are satisfied and this leads to (1). To prove (2), we suppose first that r k < q for all k. Let J be a maximal set of {1, .…”
Section: 2mentioning
confidence: 99%
“…Further generalizations to the anisotropic settings were obtained in Albuquerque et al (2014) and the best known estimates for C K,m,p can be found in Pellegrino (2014, 2017) and Cavalcante et al (2016). The case m < p < 2m was recently explored in Dimant and Sevilla-Peris (2016) and the constants involved were further explored in Albuquerque et al (2017), Nunes (2017), among others.…”
Section: Introductionmentioning
confidence: 95%